Food system policy baseline assessment: Report from Vietnam - Pham, Huong Thi Mai; Huynh, Tuyen Thi Thanh; Duong, Thanh Thi; Kawarazuka, Nozomi; de Haan, Stef; Dang, Chien Duc; Béné, Christophe (International Center for Tropical Agriculture, 2018)
The objective of this policy baseline assessment was to provide a snapshot of the views and perceptions of policy-makers and key-actors in different domains directly related to food system in Vietnam. This work contributes in Vietnam to the Food System for Healthier Diet flagship implemented as part of the Agriculture for Nutrition and Health (A4NH) CGIAR Research Programme.